Stability Control of Frequency and Voltage in Wind Power Plant Using Complementary Load with Pid Control, Pwm and Thingspeak Monitor - Yuli Hermanto; Agus Kiswantono (Fakultas Teknik Universitas Bhayangkara, 2022)
Utilization of wind energy (wind) that blows from a certain height which is then used to turn wind turbines and converted into electrical energy or so-called wind power plants (PLTB) is one solution to the problem of the energy crisis so far. In addition, voltage stability is very necessary in the continuity of the use of power plants. Unstable voltage and frequency make electrical equipment (load) easily damaged. There are various ways to reduce instability, one of which is using a pseudo/complementary load electronic control circuit. The point is that the generator will be loaded with a total load that is always constant, the load on the consumer plus the complementary (pseudo) load is equal to the nominal capacity of the generator. This research uses a 3 phase generator and a 3 phase induction motor as a driving machine, the main load uses a lamp and the pseudo load uses a heater. The main control uses a Dspic30f4012 microcontroller connected to a voltage sensor. The microcontroller works using PWM with feedback using PID, which then PWM provides pulse information to the load drive circuit. The use of PID in this control system will produce a voltage in the generator at 50 Hz and 220Vac whether there is a load or not. So that the voltage supplied to consumers is stable and does not damage electronic equipment.